A case of Capnocytophaga canimorsus endocarditis in a non-immunosuppressed host: the value of 16S PCR for diagnosis. Issue 5 (4th May 2021) - McNicol, Mark; Yew, Peter; Beattie, Gwyn; Loughlin, Laura
Abstract : Capnocytophaga canimorsus is a rare cause of endocarditis and is particularly unusual in non-immunosuppressed hosts. It is associated with animal bites, particularly those from dogs. This case describes a healthy 59-year-old woman, with no identifiable risk factors or dog bite history, who presented with fever of unknown origin. Echocardiography demonstrated an aortic valve mass and root abscess, in keeping with endocarditis, requiring urgent valve replacement surgery. Eight sets of blood cultures were drawn in total; after prolonged incubation, one set grew C. canimorusus . There was initial uncertainty over this being the causative organism, given the lack of immunosuppression or dog bite history, but 16S PCR of the valve identified the same organism, permitting targeted treatment. This case highlights the value of valve 16S PCR as a diagnostic tool in endocarditis.